Proteomic profile of an acute partial bladder outlet obstruction - Al-Saikan, Bader; Tredget, Edward; Fahlman, Richard; Ding, Jie; Metcalfe, Peter (Canadian Urological Association Journal, 2015)
Introduction: Partial bladder outlet obstruction (pBOO) is a ubiquitous problem in urology. From posterior urethral valves to prostatic hypertrophy, pBOO results in significant morbidity and mortality. However, the pathophysiology is not completely understood. Proteomics uses mass spectrometry to accurately quantify change in tissue protein concentration. Therefore, we have applied proteomic analysis to a rodent model to assess for protein changes after a surgically induced pBOO. We hypothesize that proteomic analysis after an acute obstruction will determine the most prevalent initial protein response and, potentially, novel molecular pathways. Methods: Sprague Dawley rats underwent a surgically induced pBOO (n = 3 per group) for 3, 7, or 14 days. Bladders were assessed for weight and urodynamic parameters. Proteomics used liquidchromatography based mass spectrometry. Polymerase chain reaction (PCR) was performed on tissue samples to confirm increased mRNA transcription. Results: Bladder weight and capacity increased over the experimental period, but no changes were seen in bladder pressure. Statistically significant increases in protein quantities were seen in 3 proteins related to endoplasmic reticulum stress: GRP-78 (3.66-fold), RhoA (1.90-fold), and RhoA-GDP (1.95-fold), and 2 cytoskeleton molecules: actin (1.7-fold) and tubulin a/b (3.01- fold). Decorin and lumican, members of the small leucine rich proteoglycan (SLRP) family, were also elevated (0.35- and 0.34- fold, respectively). Real-time PCR data confirmed protein elevation. Conclusion: Our experiment confirms that molecular changes occur very soon after the initiation of pBOO, and implicates several molecular pathways. We believe these insights may provide insight into novel prevention and treatment strategies targeted at the pathophysiology of pBOO.